2020
DOI: 10.1177/2050312120960656
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the challenges to successfully teaching about genetic diversity among Japanese junior high school students

Abstract: Objectives: Creating a diverse and inclusive symbiotic society is specified in the sustainable development goals. In a symbiotic society, support for those who need, it is called “reasonable support.” However, it is unclear in the classroom that many children understand “reasonable” as a consideration to support children with special needs. The aim of this study is to identify the actual understanding of junior high school students and the challenges related to genetic diversity through school health teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Genetic education for the enhancement of health literacy may be provided most effectively through school education [ 15 ]. However, genetic education was only recently introduced into the school curriculum in limited cases [ 16 , 17 ]. Furthermore, by the time these children become adults, their knowledge may already be outdated.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic education for the enhancement of health literacy may be provided most effectively through school education [ 15 ]. However, genetic education was only recently introduced into the school curriculum in limited cases [ 16 , 17 ]. Furthermore, by the time these children become adults, their knowledge may already be outdated.…”
Section: Introductionmentioning
confidence: 99%
“…First, they decided on the overall rules and everyone followed suit. This is a norm for many Japanese organizations [42][43][44][45] and an important means to prevent confusion in an emergency. Meanwhile, emergency managers working with community nonprofit organizations and research teams have shown a keen interest in engaging in disaster preparedness outreach with community members, and participatory planning has been reported to be important to ensure fair recovery and mitigation [46].…”
Section: Discussionmentioning
confidence: 99%
“…The subject matter for this course was designed for students new to human genomics, to learn how to link the genetics topics they had already studied in biology [ 25 ] with the genetics of human heredity and its relationship to nursing care. In practice, it is challenging for nurses to make a connection between the genetics that they study in biology and their actual nursing activities [ 26 ].…”
Section: Methodsmentioning
confidence: 99%